Embedding a Linkage to Preexposure Prophylaxis Care Intervention in Social Network Strategy and Partner Notification Services: Results From a Pilot Randomized Controlled Trial. (1st February 2021) - Teixeira da Silva, Daniel; Bouris, Alida; Ramachandran, Arthi; Blocker, Olivia; Davis, Billy; Harris, James; Pyra, Maria; Rusie, Laura K.; Brewer, Russell; Pagkas-Bather, Jade; Hotton, Anna; Ridgway, Jessica P.; et al.
Abstract : Background: Increased preexposure prophylaxis (PrEP) uptake among black men who have sex with men and black transgender women (BMSM/TW) is needed to end the HIV epidemic. Embedding a brief intervention in network services that engage individuals in HIV transmission networks for HIV/ sexually transmitted infections testing may be an important strategy to accelerate PrEP uptake. Setting: Partner Services PrEP study is a pilot, randomized, control trial to improve linkage to PrEP care among BMSM/TW presenting for network services in Chicago, IL, from 2015 to 2017. Methods: BMSM/TW (N = 146) aged 18–40 years were recruited from network services (partners services and social network strategy services). Intervention participants developed an individualized linkage plan based on the information–motivation–behavioral skills model and received minibooster sessions. Control participants received treatment as usual. Sociodemographic, behavioral, and clinical factors were examined at baseline and 3- and 12-month postintervention. Intent-to-treat analyses examined linkage to PrEP care within 3-month postintervention (primary outcome). Secondary outcomes were PrEP initiation, time to linkage to PrEP care, and time to PrEP initiation. Results: Compared with control participants, a significantly greater proportion of the intervention participants were linked to PrEP care within 3 months (24% vs. 11%; P = 0.04) and initiated PrEP (24% vs. 11%; P = 0.05). Among those linked to PrEP care within the study period, intervention participants were linked significantly sooner than control participants [median (interquartile range) days, 26.5 (6.0–141.8) vs. 191.5 (21.5–297.0); P = 0.05]. Conclusion: Study results support the preliminary efficacy of Partner Services PrEP to improve linkage to PrEP care and PrEP initiation among BMSM/TW. Abstract : Supplemental Digital Content is Available in the Text.